Making waves in the Mekong Delta: recognizing the work and the actors behind the transfer of Dutch delta planning expertise. Issue 9 (29th July 2019) - Hasan, Shahnoor; Evers, Jaap; Zegwaard, Arjen; Zwarteveen, Margreet
Abstract : The government of the Netherlands actively promotes Dutch delta planning to other deltaic countries. This paper describes and analyzes the Dutch–Vietnamese interactions and relationships around the development of the Mekong Delta Plan as a case of policy transfer. The paper uses an approach that regards policy transfers as processes of translation. It draws attention to the work that goes into making Dutch delta expertise and knowledge useful elsewhere. The paper shows that the financial and political support for Dutch Delta Planning expertise in Vietnam needed to be actively and continuously wielded to keep the process going. We conclude that there is merit in understanding policy transfer as a process of translation between many actors, all of whom change, learn, and influence not just each other but also what is transferred. Such an understanding allows better acknowledgement of the deeply dialogic and relational character of policy transfer processes.